Long term athlete development for equestrian riders, drivers and vaulters. A framework for the British Equestrian Federation - Wilson, C.; Edwards, D.; Collins, T.
Section 1: Generic Issues in Long Term Athlete Development 2 The 10 Year Rule 7 3 Specialisation 8 4 Physical Literacy 10 5 Developmental Age 11 6 Table 1: Development Characteristics in Late Childhood 13 7 Table 2: Development Characteristics in Early Adolescence 14 8 Table 3: Development Characteristics in Late Adolescence 16 9 Table 4: Development Characteristics in Early Adulthood 17 10 Windows of Trainability 18 11 Planning & Structuring Competition 20 12 The Talent Development Environment 21 13 Transition 23 14 The Role of Coaches and Family 24 Section 2: An Exemplar of the Long Term Athlete Development Model 15 The Generic Long Term Athlete Development Model 27 Section 3: The Equestrian Long Term Athlete Development Framework 16 Learning & Training to Ride Framework 31 17 Learning & Training to Ride 33 18 Equestrian Long Term Athlete Development Stage 1: Learning & Training to Ride 35 19 Equestrian Long Term Athlete Development Stage 1: Learning & Training to Ride 36 20 Riding and Training to Compete 37 21 Equestrian Long Term Athlete Development Stage 2: Riding & Training to Compete 39 22 Equestrian Long Term Athlete Development Stage 2: Riding & Training to Compete 40 23 Riding & Training to Win 41 24 Equestrian Long Term Athlete Development Stage 3: Riding & Training to Win 43 25 Equestrian Long Term Athlete Development Stage 3: Riding & Training to Win 44